2014
DOI: 10.1634/theoncologist.2013-0229
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computed Tomography and Biomarkers for Early Treatment Response Evaluation in Metastatic Colon Cancer

Abstract: Purpose. The indication for liver transplantation in malignant liver tumors has been controversial due to disappointing results and shortage of donor organs. The authors evaluated the experience and results of a single center in order to define present indications and selection criteria in hepatobiliary malignancy. Patients and Methods. Retrospective analysis of 212 patients who underwent liver transplantation for malignant tumors between 1972 and 1995: Primary hepatobiliary tumors: hepatocellular carcinoma, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In the current study, target lesions were defined on the baseline FDG PET-CT according to strict criteria: FDG avidity (higher than two times the normal liver/thoracic aorta uptake) and size (more than 15 mm). More recently, some studies showed that an FDG PET-CT evaluation after a single course of chemotherapy is able to discriminate, with a high NPV, patients unlikely to benefit from the treatment in terms of both tumoural shrinkage and general outcome (PFS/OS) [ 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, target lesions were defined on the baseline FDG PET-CT according to strict criteria: FDG avidity (higher than two times the normal liver/thoracic aorta uptake) and size (more than 15 mm). More recently, some studies showed that an FDG PET-CT evaluation after a single course of chemotherapy is able to discriminate, with a high NPV, patients unlikely to benefit from the treatment in terms of both tumoural shrinkage and general outcome (PFS/OS) [ 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum SUV (SUV max ) of all target lesions within a patient was then summed and served as a measure of tumor burden at the baseline time point, referred to as SUV max Total. Note that SUV max has been commonly used, particularly at the time this study was conducted, to evaluate tumor burden and change in tumor burden by PET [ 3 7 , 12 , 23 ]. Nontarget lesions were noted, and the anatomical location of both target and nontarget lesions was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Of these articles, 12 were on non-small cell lung cancer (NSCLC) (49.48% of patients),2,3,16,18,19,21,22,24,26,27,35,38 two on malignant glioma (5.90% of patients),23,34 two on metastatic colorectal cancer (CRC) (7.63% of patients),31,36 two on gastrointestinal stromal tumor (GIST) (7.28% of patients),29,30 two on metastatic renal cell carcinoma (RCC) (9.60% of patients),25,37 and five on other solid tumors (metastatic gastric adenocarcinoma, metastatic breast cancer, metastatic melanoma, biliary tract cancer, and mixed kinds of tumors; 20.12% of patients) 17,20,28,32,33. Meanwhile, all of these articles coped with molecularly targeted therapy: six with erlotinib,3,16,21,22,24,27 six with bevacizumab,23,26,28,31,34,36 four with gefitinib,2,19,35,38 three with imatinib,17,29,32 two with sunitinib,25,30 one with cetuximab,33 and three with mixed kinds of molecularly targeted agents 18,20,37. PET-CT/PET was performed pretherapy and posttreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the absence of consensus on metabolic response criteria, the participants were assigned to PET response or PET nonresponse group based on the change of SUVmax in each article. Of all the eligible studies, 17 provided an extractable HR value for PFS,3,16,18,20,21,2326,28,3032,35,36,38 19 for OS,2,3,16,17,19,2128,31,3337 and five for TTP 2,17,27,29,33. The principal characteristics and further details are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%